Randomized multicenter trial to assess posterior capsule opacification and glistenings in two hydrophobic acrylic intraocular lenses - Auffarth, Gerd U.; Brézin, Antoine; Lignereux, François; Khoramnia, Ramin; Yildirim, Timur Mert; Kohnen, Thomas; Bianco, Jessica (Scientific reports, 2023)
To evaluate the long-term posterior capsule opacification (PCO) formation, and glistening rate of the HOYA Vivinex (XY1) IOL compared to Alcon AcrySof (SN60WF). In this prospective, multicentric, randomized, paired-eye, open-label study, we included 87 subjects that underwent cataract surgery with IOL implantation, with 67 patients completing the 3-year follow-up. The completer population consisted of 32 subjects implanted with XY1 and 35 implanted with SN60WF. Primary endpoints consisted of the evaluation of glistenings and measurement of PCO. Secondary outcomes included Best Corrected Distance Visual Acuity (BCVA), Contrast Acuity (CA), uncorrected visual acuities, subjective refraction, medical and lens complication rates, adverse events, and optical/visual symptoms. Follow-up visits occurred at 6-months, 1-, 2- and 3-years. At 3-years follow-up, mean PCO score was 0.121 ± 0.193 for eyes implanted with Vivinex versus 0.239 ± 0.463 for AcrySof (p = 0.026). The Vivinex IOL showed statistically significantly lower glistening occurrence through 3-years postoperatively (0.14 ± 0.26) compared to AcrySof (1.79 ± 1.43; p < 0.0001). Postoperative visual acuities improved from baseline in both IOL groups (p < 0.0001), and remained stable through the 3-year follow-up period. Eyes implanted with a HOYA Vivinex IOL exhibited significantly lower occurrence of glistening at 3-years versus Alcon AcrySof (p < 0.0001). Incidence of PCO was very low and comparable in both Vivinex and AcrySof eyes.
Gesehen am 22.06.2023